2021
DOI: 10.20899/jpna.7.2.192-204
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Financial Burden in Nonprofit Sector Commitment

Abstract: Evidence about millennial work motivations and the increasing importance of compensation questions the durability of the donative labor hypothesis in explaining nonprofit sector commitment. Nonprofit graduate education offers an employment pipeline into the sector, but what if the importance of compensation is partly driven by the financial burden accrued from education? Could it be that financial burden contributes to choices about work and commitment to the nonprofit sector? Using longitudinal data of nonpro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…One potential explanation that future research should further investigate is that married individuals may have an additional safety net, be it through additional income or health care benefits, which would indicate that employment-related changes can be buffered more easily. Our findings on pay and commitment align with earlier work indicating that the relationship between pay and commitment is complex and not clear cut (Kuenzi et al, 2021b). Nonprofit workers have long been found to be motivated by doing good and having an impact (Tschirhart et al, 2008).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…One potential explanation that future research should further investigate is that married individuals may have an additional safety net, be it through additional income or health care benefits, which would indicate that employment-related changes can be buffered more easily. Our findings on pay and commitment align with earlier work indicating that the relationship between pay and commitment is complex and not clear cut (Kuenzi et al, 2021b). Nonprofit workers have long been found to be motivated by doing good and having an impact (Tschirhart et al, 2008).…”
Section: Discussionsupporting
confidence: 88%
“…Whereas they are mostly aligned, sector choice and sector commitment are not the same (Kuenzi, Walk, & Stewart, 2021b). Prior research has found low compensation (AbouAssi, McGinnis Johnson, & Holt, 2021;Johnson & Ng, 2016;Walk et al, 2021), limited professional development opportunities (Linscott, 2011), and the financial burden of higher education (Berkshire, 2012;Kuenzi et al, 2021b) disrupt the initial choice to work in the nonprofit sector from being a sustained commitment. Moreover, Kuenzi, Walk, and Stewart (2021b) found that nonprofit sector commitment changes over time, indicating that commitments may change in the face of new circumstances, such as the COVID-19 pandemic.…”
Section: Nonprofit Work: Choice and Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of nonprofits, we have evidence about the general stress of the pandemic to the sector as a whole and for organizations (e.g., see Grønbjerg et al, 2021 ; M. Kim & Mason, 2020 , Kuenzi et al, 2021 ; Stewart, Kuenzi, Walk, & Klippel, 2021 ), but limited evidence about how nonprofit workers have fared. One such example is from Varela Castro et al (2022) who examined the provision of emotional labor of frontline healthcare workers and the toll this took on them.…”
Section: Introductionmentioning
confidence: 99%
“…The authors conclude by discussing the implications of their findings for enhancing NASPAA's core competencies to further expand their accreditation system globally. Kuenzi et al (2021) examine the public service motivation of millennials and how the financial burden accrued from graduate school influences their willingness to work in the nonprofit sector for comparatively lower wages than perhaps could be earned through private sector employment. On the basis of the donative labor hypothesis, the authors find important differences in nonprofit sector commitment and sector choice while also noting the relationship between the two.…”
mentioning
confidence: 99%